Traditional and popular cultural discourses within the post-war development of Japan’s cultural diplomacy - Zykas, Aurelijus (Acta Orientalia Vilnensia, 2011)
Vytautas Magnus University This paper analyses the development of post-war Japan’s cultural diplomacy since 1945, dividing it into four stages. It raises questions about what government institutions have been conducting cultural diplomacy, what the main international challenges have been, what communication tools have been used, and what kind of cultural discourses were prevalent during a particular stage. Special emphasis is put on the division of traditional versus popular cultural discourses within the cultural diplomacy of Japan, mainly concentrating on the important shift in this aspect that occurred at the beginning of the 21st century. This shift was marked by the government’s increasing shift towards popular culture discourse and the deliberate exploitation of that to promote Japan in the world.